Study on Uniform Resource Model Design Method Based on Major Class and Metadata - Yanbin Shi; Gengshu Su; Ling Li; Yijie Jiang (Dianxin kexue)
Firstly, the bondage of the unified resource model were researched, which were hard modeling and using physical and logical class as the top class. Secondly, the methods were put forward that are major class modeling and meta data driving and using geometric shape as the top class. Lastly, the over view of the unified resource model was designed and the sticking points were given, that were unified ware model and unified link model and restored physical object and logical object and compatible with the entire network.